Pengaruh Kualitas Produk dan Layanan terhadap Kepuasan dan Loyalitas Konsumen Pada Pengembang PT Araya Bumi Megah Malang - Murtiyanto, Rizky Kurniawan; Rochman, Fatchur; Susilowati, Christin (Jurnal Aplikasi Manajemen, 2014)
The study is to examine and analyze the effect of product quality and service quality to customer satisfaction, examine and analyze the effect of product quality and service quality to customer loyalty on developer PT. Araya Bumi Megah Malang. Research study conducted including an explanation (explanatory research) that explain the causal relationship between variables through the course of a study testing the hypothesis of this study used a sample of 34 respondents, while sampling technique using purposive sampling. Data analysis is the analysis of PLS (Partial Least System). The results of this study were (1) product quality have a significant influence to customer satisfaction (2) service quality has a significant influence to customer satisfaction (3) product quality has a significant influence to consumer loyalty (4) service quality has a significant influence to customer loyalty (5 ) consumer satisfaction has a significant influence to consumer loyalty (6) product quality has a significant effect to customer loyalty when through customer satisfaction (7) service quality has a significant influence on customer loyalty when through customer satisfaction.